Ansichten eines Clowns. Roman - Böll, Heinrich (1917-1985) (Munich DTV, 1967)
'Ansichten eines Clowns' tells the story of Hans Schnier, a man whose love and relationship with Marie Derkum—and ultimately his own sense of self—are undone by the value-driven postwar society of the 1950s and 1960s. Rejecting his affluent family's ambitions shaped by the "Wirtschaftswunder," Hans chooses the unconventional path of a comedian instead of pursuing a career in politics or business. His six-year relationship with Marie, a devout Catholic, begins to unravel when their differing values clash over marriage and child-rearing. Despite Hans’s willingness to compromise, Marie leaves him, marking the start of his downward spiral into alcoholism and professional decline. Over the course of a few hours in Bonn, Hans reflects on his life, calling old acquaintances and confronting the hypocrisy of postwar Germany, where former Nazis reinvent themselves, and societal values shift without genuine reflection. The novel critiques the lack of accountability for the Nazi past, blind religious obedience, and the moral compromises of the era. It ends poignantly with Hans playing guitar on the steps of Bonn's train station, waiting in vain for Marie’s return, while passersby mistake him for a beggar.
Originally published in 1963
Keywords: 20th Century (1901-2000); Novel; Psychology; World War II (1939-1945); Germany